Quorum Sensing Inhibitors as Anti-Biofilm Agents - Brackman, Gilles; Coenye, Tom (Current Pharmaceutical Design, 2015)
Biofilms are microbial sessile communities characterized by cells that are attached to a substratum or interface or to each other, are embedded in a self-produced matrix of extracellular polymeric substances and exhibit an altered phenotype compared to planktonic cells. Biofilms are estimated to be associated with 80% of microbial infections and it is currently common knowledge that growth of micro-organisms in biofilms can enhance their resistance to antimicrobial agents. As a consequence antimicrobial therapy often fails to eradicate biofilms from the site of infection. For this reason, innovative anti-biofilm agents with novel targets and modes of action are needed. One alternative approach is targeting the bacterial communication system (quorum sensing, QS). QS is a process by which bacteria produce and detect signal molecules and thereby coordinate their behavior in a cell-density dependent manner. Three main QS systems can be distinguished: the acylhomoserine lactone (AHL) QS system in Gram-negative bacteria, the autoinducing peptide (AIP) QS system in Gram-positive bacteria and the autoinducer-2 (AI-2) QS system in both Gram-negative and -positive bacteria. Although much remains to be learned about the involvement of QS in biofilm formation, maintenance, and dispersal, QS inhibitors (QSI) have been proposed as promising antibiofilm agents. In this article we will give an overview of QS inhibitors which have been shown to play a role in biofilm formation and/or maturation.
Keywords: quorum sensing inhibition